Nǣothāng kānčhatkān singwǣtlō̜m phūmithat mư̄ang yāng yangyư̄n nai phư̄nthī Thētsabān Nakhō̜n Phra Nakhō̜n Sī ʻAyutthayā, Čhangwat Phra Nakhō̜n Sī ʻAyutthayā (Samnakngān Nayōbāi læ Phǣn Sapphayākō̜n Thammachāt læ Singwǣtlō̜m, 2012)
On management and development of natural resources, environment, and landscape in Phra Nakhon Si Ayutthaya Province, Central Thailand.